Location - based system for mobile devices using RFID - Seyed Hossein Siadat, 1983-, author; Ali Selamat, author; Asia Modelling Symposium (2008 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL